Main Price and Non-Price Factors of the Renewable Energy Sources Development in Union Countries of the European - Vladimir Nikolaevich Zuev; Tikhon N. Kanikhin (Регионология, 2025)
Introduction. The article examines the main price and non-price factors of renewable energy development in the EU countries at the present stage. The relevance of studying RES is determined, on the one hand, by the importance of environmental protection within the global climate agenda, on the other hand, by the insufficient coverage of this topic in science. The aim of the study is to identify the main price and non-price factors that ensure the development of RES in the EU countries; the hypothesis is that the volatility of hydrocarbon prices and EU imports of traditional energy sources from Russia is the main factor of RES development in the EU countries.